Long‐term pockmark maintenance by fluid seepage and subsurface sediment mobilization – sedimentological investigations in Lake Neuchâtel. Issue 5 (14th February 2016) - Loher, Markus; Reusch, Anna; Strasser, Michael
Abstract: Pockmarks and mud volcanoes from marine and lacustrine environments are thought to be the surface expression of focused fluid flow (gas and/or water). However, the control fluid flow exerts on the sediment dynamics and rates of activity of such features, especially the maintenance and growth of pockmarks, is not well understood. This study suggests that variable fluid flow is the driving process that has maintained two lacustrine pockmarks over thousands of years. In Lake Neuchâtel (western Switzerland), the currently active Chez‐le‐Bart Pockmark (diameter ca 160 m, depth ca 10 m) and the Treytel Pockmark (diameter ca 100 m, depth ca 4 m) indicate 'quiescent' fluid flow as well as past, 'eruptive', events of subsurface sediment mobilization. This study aims to test the hypothesis that phases of increased fluid flow through the pockmarks have led to the remobilization and spilling of sediment over the pockmark rims, and that different modes of activity phases are responsible for their maintenance and growth. So termed 'subsurface sediment mobilization deposits' are visible in seismic profiles and correlate to specific, sedimentary intervals in Kullenberg‐type long piston cores. In a detailed analysis, different modes of transport are recognized, which are attributed to high‐density flows that correspond to multiple pulses of activity. The pockmark morphology, seismic stratigraphy and core correlation with pre‐existing data reveals that the two pockmarks have been maintained throughout the Holocene and underwent several switches between 'quiescent' and 'eruptive' mode activity.